Selecting COTS components: a comparative study on E-Payment systems - Cechich, Alejandra (2003)
Using COTS software promises faster time-to-market, which can yield substantial advantages over competitors with regards to earlier placement of a new product on a market. At the same time, component-based software introduces risks, such as unknown quality properties of the components in use, that can inject harmful side effects into the final product. The purpose of a COTS selection is to analyse several candidates to identify the most suitable components to be integrated. This paper presents two of the most representative COTS selection methods, which have been used to select COTS components for an E-Payment system. The role of this case discussion is to offer some guidelines related to the use of the methods for a COTS-based development process.